Effects of Thiopurine Methyltransferase (TPMT) Polymorphism on Red Blood Cells and Plasma Concentration of 6-Mercaptopurine: Clinical Study - Mohammed Khudair Hasan (Journal of Global Pharma Technology, 2018)
Objective: This study was aimed to find out the proper dosing strategy for patients with ALL treated with 6-mercaptopurine with possible genotype polymorphisms and the relationship between genotype and toxicity. Material and Methods: Sixty ALL patients and sixty healthy subjects were enrolled. The subjects involved two groups; group A Includes 60 patients with acute lymphoblastic leukemia on maintenance (continuation) phase (2:1 Male: Female ratio); group B Includes 60 healthy subjects' adults and children without any medical illnesses (2:1 Male: Female ratio). DNA was isolated from whole blood and genetic polymorphism in thiopurine S-methyltransferase (TPMT) coding genes were detected by polymorphism chain reaction-restriction fragment length (PCR-RFLP) assay. Complete blood count, liver function tests, renal function tests and blood sugar concentration obtained at the same day of blood sampling for patient and control subjects were done. Results: TPMT polymorphisms were seen in 14 (23.33%) of the total study population. The number of patients with TPMT*2 was 8 (13.33%), whereas, patients with TPMT*3B was 6 (10.00%). As a comparison between patients with TPMT polymorphism to patients without TPMT polymorphism, Hepatotoxicity and nephrotoxicity increased significantly in patients with TPMT polymorphism. Random blood sugar was significantly higher in patients with TPMT polymorphism (p = 0.02894). Bone marrow suppression was significantly higher in patients with TPMT polymorphism. 6-TGNs concentrations were increased significantly in the patients with TPMT polymorphisms using 6-MP (p = 0.00667). A significant positive relationship was founded between 6- TGNs RBC concentration and serum creatinine concentration (r= 0.9340), serum concentration of ALT, AST, ALP plasma concentration and TSB (r= 0.7428, 0.6250 0.6509 and 0.435) Conclusions: In this study, we report a presence of the TPMT2 and TPMT 3B polymorphism in Iraqis population. Therefore, TPMT variants monitoring is important to avoid the development adverse effects in patients treated with thiopurine drugs.Keywords: TPMT gene, 6- Mercaptopurine, Thiopurine drugs, Polymorphisms, Acute lymphoblastic leukaemia.